Therapeutic Potentials of Triterpenes in Diabetes and its Associated Complications - Putta, Swathi; Sastry Yarla, Nagendra; Kumar Kilari, Eswar; Surekha, Challa; Aliev, Gjumrakch; Basavaraju Divakara, Madhihalli; Sridhar Santosh, Mysore; Ramu, Ramith; Zameer, Farhan; Prasad MN, Nagendra; Chintala, Ramakrishna; Vijaya Rao, Pidugu; et al. (Current Topics in Medicinal Chemistry, 2016)
Diabetes is a major chronic metabolic disorder globally and around of 285 million people are affected by the disease and the number is expected to double in the next two decades. The major focus of anti-diabetic therapies is to enhance insulin production, sensitivity and/or reduce the blood glucose level. Although several synthetic drugs have been developed as antidiabetic agents but their utility has been hampered due to their side effects and poor efficacy. In this scenario, research on natural products has been gained importance due their safety profile in toxicity studies. Terpenoids belong to an important class of natural products and several terpenoids have been reported as antidiabetic agents. Some of them are under various stages of pre-clinical and clinical evaluation to develop them as antidiabetic agents. These agents can inhibit enzymes responsible for the development of insulin resistance, normalization of plasma glucose and insulin levels and glucose metabolism. Triterpenes can act as promising agents in the treatment of diabetic retinopathy, neuropathy and nephropathy or in impaired wound healing by inhibiting several pathways involved in the diabetes and associated complications. However, efforts in understanding the biological actions and clinical studies involving the applications of triterpenes in treating diabetes are very limited. Hence, special attention is imperative to explore the therapeutic potential of these compounds and provide new information to the scientific community. This review aims to provide the recent advances in triterpenes chemistry, its derivatives, biological interventions and its therapeutic applications with special emphasis on diabetes and its associated disorders.
Keywords: Diabetes